2013
DOI: 10.1016/j.vetimm.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ clonality is associated with prolonged acute plasma viremia and altered mRNA cytokine profiles during the course of Feline Immunodeficiency Virus infection

Abstract: Acute lentiviral infection is characterized by early CD8+ cytotoxic T cell (CTL) activity and a subsequent decline in plasma viremia. However, CD8+ lymphocytes fail to eliminate the virus and a progressive T cell immune dysfunction develops during the course of chronic lentiviral infection. To further define this CD8+ immune dysfunction we utilized PARR (PCR for Antigen Receptor Rearrangements), a technique which measures clonally expanded lymphocyte populations by comparison of highly conserved T cell recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We and others have previously established that CD8 + T cells exhibit an activated phenotype during the course of FIV infection (23, 62, 63). Therefore, the focus of this investigation was to demonstrate how Treg cells may utilize CD8 + T cell activation as a route for CD8 + T cell suppression.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously established that CD8 + T cells exhibit an activated phenotype during the course of FIV infection (23, 62, 63). Therefore, the focus of this investigation was to demonstrate how Treg cells may utilize CD8 + T cell activation as a route for CD8 + T cell suppression.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 187 Much data indicates that clonality is not synonymous with malignancy and it has been shown that any strong chronic antigenic stimulation can promote selective proliferation of lymphocyte clones. Benign clonal expansions have been documented in humans, 188 , 189 , 190 , 191 , 192 , 193 dogs, 194 , 195 , 196 and cats with infectious diseases 197 (e.g., ehrlichiosis, leishmaniasis, feline immunodeficiency virus), chronic inflammatory intestinal disorders, neoplasia, and drug administration. In addition, it has been reported that inflammatory and low‐grade neoplastic lymphoid lesions can coexist in the same cat.…”
Section: Resultsmentioning
confidence: 99%
“…FIV+ animals were infected with the NCSU 1 isolate of FIV. Each cat was administered 1X10 5 TCID 50 intravenously of cell-free virus as previously described [13,14]. At the time of these studies, all cats had been infected for 1-3 years and were in the chronic stage of infection.…”
Section: Study Animalsmentioning
confidence: 99%